Gestión de abastecimiento del Almacén Cómplices de Amor, de la ciudad de Milagro, periodo 2023. - Ramos Miguez, Vanely Virginia (2024)
Small micro - enterprises tend to have problems during the procurement of raw materials, to meet their production of products, reason that occurs due to the lack of management that exists within the company, this case study entitled "Supply Management Warehouse Accomplices Of Love, From The City Of Milagro, Period 2023" has as general objective the analysis of supplies through observation and research tools during the acquisition of materials made in the entity. The correct supply management in SMEs helps to have a balance and good management of its stock through a stable relationship with its suppliers and the optimization of time and cost of supplies. This case study is framed under the established guidelines of the Technical University of Babahoyo with which it has been possible to determine and know the problematic factors that occur in the store Complies de Amor, this identification of deficits in their supply management has caused losses of both supplies and customers. For this reason, this case study will propose that the company performs a continuous monitoring of suppliers, keeps a record of its inventory and among others that will be detailed in the outcome of this document. A good supply management guarantees the efficiency of the companies, improves its image before the competition, and generates the loyalty of its customers to the organization.